Changing attitudes about the impact of women's employment on families: The COVID‐19 pandemic effect. Issue 6 (30th June 2022) - Vandecasteele, Leen; Ivanova, Katya; Sieben, Inge; Reeskens, Tim
Abstract: We use representative longitudinal panel data from the Dutch European Values Survey (EVS) to study whether the COVID‐19 pandemic shifted opinions about how a woman's full‐time employment impacts family life. The data was collected before the COVID‐19 pandemic in 2017 and in May 2020. The analysis focuses on groups whose unpaid and paid work situation changed abruptly with the COVID‐19 pandemic: parents with coresident children, and those who experienced a change in paid workload that clashes with traditional gender role expectations, namely women whose workload increased and men whose workload decreased or who stopped working. We found that groups that faced an abrupt change in their paid and unpaid work routines that clashed with their previously held gender attitude changed their gender attitude in alignment with the new paid or unpaid work situation. For women in couple households with children, this meant that they saw a halt in their progression toward gender egalitarian attitudes. For those who experienced a change in paid workload that clashes with traditional gender role norms, it meant stronger progression toward gender egalitarian attitudes. The results are interpreted on the basis of cognitive dissonance theory and exposure theory and placed in the context of previous findings.